CURRENT ASPECTS OF TRANSFORMATION OF ECONOMIC RELATIONS: CRYPTOCURRENCIES AND THEIR LEGAL REGULATION - N. M. Pantielieieva; N. V. Rogova; S. M. Braichenko; S. V. Dzholos; A. S. Kolisnyk (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
The article is devoted to the analysis of transformation of economic relations due to the emergence of such phenomenon as cryptocurrency. It is substantiated that its appearance is connected with the development of the information society, the formation of the virtual economy and the spread of digitization processes in all spheres of economic activity. It is proved that despite the innovative nature of the revolutionary character and the considerable potential for stimulating radical changes in the sphere of economic relations and economic model of modern society, the cryptocurrency is a confirmation of the evolution of money. From the point of view of the theory of money, the ability of cryptocurrency to perform the functions of money (measures of value, means of payment and medium of exchange, accumulation, world money), as well as new specific functions — social, regulatory, indicative and others, — have been proved.